DDRE-06. TARGETING THE SPHINGOLIPID BALANCE VIA ACID CERAMIDASE INHIBITION TO DECREASE GROWTH OF TMZ-RESISTANT GLIOBLASTOMA AND BLOCK MIGRATION. (12th November 2021) - Hawkins, Cyntanna; Jones, Amber; Ziebro, Julia; Gordon, Emily; Libby, Catherine; Williford, Sarah; Allegood, Jeremy; Cooper, Sara; Ramanadham, Sasanka; Doan, Ninh; Hjelmeland, Anita
Abstract: Dysregulated sphingolipid metabolism is associated with many cancers; allowing cells to evade apoptosis through increases in sphingosine-1-phosphate (S1P) and decreases in ceramides. Ceramides can be hydrolyzed by ceramidases to sphingosine, which can then be phosphorylated by sphingosine kinases to S1P. S1P allows cells to evade apoptosis and increase migration, while shifts toward ceramides favor cell death. Glioblastoma (GBM) exhibits shifts in the sphingolipid balance towards S1P, contributing to chemoresistance and migration. Understanding of sphingolipid metabolism in GBM is still limited, and currently, there are no approved treatments to target the dysregulation. Acid ceramidase (ASAH1), a key enzyme in the production of S1P, is highly expressed in GBM and is associated with worse survival of GBM patients, as per The Cancer Genome Atlas data. To address the altered sphingolipid metabolism and therapeutic resistance in GBM, we explored the efficacy of pharmacologic and genetic inhibition of ASAH1 in both parental and temozolomide (TMZ)-resistant patient-derived xenografts. Cells were infected with ASAH1 shRNA or treated with ASAH1 inhibitors and assessed for cell growth and migration. Our work suggests that pharmacologic inhibition of ASAH1 induces cell death and that this effect is maintained in TMZ-resistant cells. Furthermore, we find a novel role for carmofur, an ASAH1 inhibitor, in the inhibition of GBM migration. Together, these data suggest the potential utility of normalizing the sphingolipid balance in the context of GBM TMZ resistance.